The rigor of science and the intuition of metaphysics (Ágora de Heterodoxias, 2015)
In this lecture, a valuable contribution to teaching and university research, the author thinks about on scientific paradigm changes and epistemic relevance of systemic realities, expiration of logical positivism, the value of rigorous, systematic and self-critical language for updated science and the same creative power of the human mind
Keywords: scientific and epistemological paradigm; systemic realities; human mind